CARACTERIZAÇÃO DO USO E OCUPAÇÃO DAS TERRAS NA SUB-BACIA DO CÓRREGO CRIMINOSO, BACIA DO RIO TAQUARI, MS, BRASIL - FERNANDES, Tatiane; GÜNTZEL, Adriana Maria; OLIVEIRA, Vincler Fernandes Ribeiro (ANAIS DO ENIC, 2020)
-